Atypical clinical presentation of mechanical small bowel obstruction with superior mesenteric vein occlusion caused by a retained free intraperitoneal staple after laparoscopic appendectomy: A case report. Issue 4 (17th March 2020) - Tamura, Koji; Nakayama, Hiromichi; Kono, Hiroshi; Kuroki, Rumi; Maeyama, Ryo; Yamamoto, Hirofumi; Ueki, Takashi; Okido, Masayuki; Ichimiya, Hitoshi
Abstract: Mechanical small bowel obstruction (SBO) is a common postoperative complication, and most cases are caused by postoperative adhesions. We herein report a case of SBO with superior mesenteric vein occlusion caused by a metal staple after laparoscopic appendectomy. A 35‐year‐old Japanese woman presented to our department with severe upper abdominal pain and vomiting. She had undergone laparoscopic appendectomy using a linear stapler 7 years before. Abdominal CT showed mild small intestinal dilation with mesenteric edema and volvulus of the small bowel mesentery. Moreover, occlusion of the superior mesenteric vein was observed. Emergency exploratory laparoscopy revealed a strangulated SBO caused by a free unformed staple. The obstruction was released by a laparoscopic technique without bowel resection. The number of laparoscopic surgeries has recently been increasing, and complications specific to laparoscopic surgery have been recognized. All spilled and unformed staples should be removed to the greatest extent possible during laparoscopic operations.